(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the information and views on the main water bodies on the territory of modern Uzbekistan - the Aral Sea, the Amu Darya, Syrdarya, Zeravshan, Kashkadarya, Chirchik rivers in foreign historical sources of the XIX - early XX centuries. The reasons for the interest of foreign researchers to these water bodies are revealed.